Inflation Uncertainty, Asset Valuations, and the Credit Spreads Puzzle - David, Alexander (Review of Financial Studies, 2008)
[Investors' learning of the state of future real fundamentals from current inflation leads to macroeconomic state dependence of asset valuations and solvency ratios of firms within given rating categories. Since credit spreads are convex functions of solvency ratios, average spreads are higher than spreads at average solvency ratios. Macroeconomic shocks carry risk premiums so that expected default losses are more sensitive to changes in the price of risk than are credit spreads. By incorporating state dependence and increasing the price of risk, the econometrician obtains high credit spreads while maintaining average default losses at historical levels–the credit spreads puzzle.]